2006
DOI: 10.1007/s00018-006-6149-9
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase: an oxidative enzyme and effector of cell function

Abstract: Lysyl oxidase (LOX) oxidizes the side chain of peptidyl lysine converting specific lysine residues to residues of alpha-aminoadipic-delta-semialdehyde. This posttranslational chemical change permits the covalent crosslinking of the component chains of collagen and those of elastin, thus stabilizing the fibrous deposits of these proteins in the extracellular matrix. Four LOX-like (LOXL) proteins with varying degrees of similarity to LOX have been described, constituting a family of related proteins. LOX is synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
480
0
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(497 citation statements)
references
References 82 publications
7
480
0
10
Order By: Relevance
“…These data indicate that SHR TA VSMCs exhibit a regulation of LOX at gene expression and proteolytic levels. Second, In contrast to previous studies, instead of a single mature‐LOX isoform as observed in most other tissues (Barker, Cox & Erler, 2012; Lopez et al., 2009; Lucero & Kagan, 2006; Payne, Hendrix & Kirschmann, 2007), we detected two forms of mature‐LOX in rat aortic VSMCs. This finding could imply that a unique mechanism may be involved in the proteolytic processing of LOX, by which different sites of pro‐LOX may be targeted and result in two different sizes of mature‐LOX.…”
Section: Discussionmentioning
confidence: 63%
“…These data indicate that SHR TA VSMCs exhibit a regulation of LOX at gene expression and proteolytic levels. Second, In contrast to previous studies, instead of a single mature‐LOX isoform as observed in most other tissues (Barker, Cox & Erler, 2012; Lopez et al., 2009; Lucero & Kagan, 2006; Payne, Hendrix & Kirschmann, 2007), we detected two forms of mature‐LOX in rat aortic VSMCs. This finding could imply that a unique mechanism may be involved in the proteolytic processing of LOX, by which different sites of pro‐LOX may be targeted and result in two different sizes of mature‐LOX.…”
Section: Discussionmentioning
confidence: 63%
“…Numerous other proteins associate with microfibrils or with elastin itself, including the microfibril associated glycoproteins (MAGPs), fibulins and EMILIN-1 (for a complete list see Kielty et al, 2002). Based on ultrastructural studies, microfibrils are thought to provide a scaffold that facilitates elastin molecular alignment and subsequent cross-linking, which is catalyzed by one or more members of the lysyl oxidase (LOX) gene family (Csiszar, 2001;Kagan and Li, 2003;Lucero and Kagan, 2006).…”
Section: Elastic Fiber Componentsmentioning
confidence: 99%
“…5 Indeed, recent findings revealed that LOX family proteins markedly influence cell behavior, including chemotactic responses, cell growth and intracellular signaling and transcription. 1,26-29 Recently, Eliades et al reported that LOX inhibition with BAPN reduces downstream signaling of platelet-derived growth factor receptor, including activation of Akt and ERK1/2 pathways, and diminishes the proliferative effect of the platelet-derived growth factor receptor on the megakaryocyte lineage, 30 suggesting that LOX proteins have a functional role in growth factor receptor signaling and cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 These proteins have a conserved C-terminal region corresponding to the catalytic domain, which includes the lysine tyrosylquinone cofactor, the copper-binding site and the cytokine receptor-like domain. 5 They exhibit different in vivo expression patterns and have different biological roles, including extracellular matrix stabilization, cell proliferation, cell growth and intracellular signal response. 5 In 2006, we reported that LOXL-1 mRNA was upregulated in pressure overloaded hypertrophied hearts induced by abdominal aortic constriction (AAC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation